The Formulation of Pacing (Costus speciosus) Extract Tablet by Using Avicel®Ph 200 As Filler-Binder and Amylum As Disintegration Agent - Damayanti, Damayanti; Sari, Ika Puspita; Sulaiman, T.N. Saifullah; Bestari, Angi Nadya; Setiawan, Irfan Muris (Indonesian Journal of Pharmacy, 2018)
Pacing (Costus speciosus) is an herbaceous plant that is native to Indonesia and it  can be used as a male contraceptive due to spermatogenesis inhibition. The purpose of this study is to find out the composition of optimum Avicel PH 200® as the filler-binder and amylum as the disintegration agent and to find out the variations on physical properties of the powder and tablet. The tablets were made by directly compression in 8 runs based on Simplex Lattice Design (SLD) from Design Expert 7.1.5, in which the test on physical properties of powder includes tapping index, water absorption, and moisture content, as well as on the physical properties of tablet, including hardness, friability, and disintegration time. The results showed that the variation in the composition between Avicel® PH 200 as the filler-binder and amylum as the disintegration agent had a significant effect on the friability of Costus speciosus (CS) extract tablet, in which the combination of both materials can increase the friability of the tablet. The optimum formula of CS tablet had a composition of Avicel® PH 200 by 462,5 mg and amylum by 37,5 mg contained in each tablet.